Study on Storage Conditions and Suitability Zoning of Shallow Floor Energy in Nanchang City - Hua Zhang; Shuren Hao; Qing Yang; Zihong Wang; Wujun Dong; Liangliang Guo (Geofluids)
In the context of China’s carbon summit strategy, as renewable clean energy, the development and utilization of shallow geothermal energy has broad prospects. Based on the analysis of the occurrence conditions of shallow geothermal energy in Nanchang City, the suitability zoning of the ground source heat pump project in Nanchang City is studied by using the analytic hierarchy process. The results show that Nanchang is very suitable for the construction of the ground source heat pump system. Among them, the suitable area of the groundwater ground source heat pump is 252.17 km2, the basically suitable area is 133.64 km2, and the unsuitable area is 124.29 km2. The suitable area of the buried pipe ground source heat pump is 180.49 km2, the basically suitable area is 320.82 km2, and the unsuitable area is 8.79 km2. The evaluation results can provide a basis for the development and utilization of shallow geothermal energy in Nanchang.